Role of SIRT1-mediated mitochondrial and Akt pathways in glioblastoma cell death induced by Cotinus coggygria flavonoid nanoliposomes - Wang G (Dove Medical Press, 2015)
Gang Wang,1,2,* Jun Jie Wang,1,2,* Tony SS To,3 Hua Fu Zhao,3 Jing Wang3 1Department of Pharmaceutics, Shanghai Eighth People’s Hospital, Shanghai, People’s Republic of China; 2College of Pharmacy, Hubei University of Medicine, Shiyan, Hubei Province, People’s Republic of China; 3Department of Health Technology and Informatics, The Hong Kong Polytechnic University, Hong Kong SAR, People’s Republic of China *These authors contributed equally to this work Abstract: Flavonoids, the major polyphenol components in Cotinus coggygria (CC), have been found to show an anticancer effect in our previous study; however, the exact mechanisms of inducing human glioblastoma (GBM) cell death remain to be resolved. In this study, a novel polyvinylpyrrolidone K-30/sodium dodecyl sulfate and polyethyleneglycol-coated liposome loaded with CC flavonoids (CCFs) was developed to enhance solubility and the antibrain tumor effect, and the molecular mechanism regarding how CCF nanoliposomes (CCF-NLs) induce apoptotic cell death in vitro was investigated. DBTRG-05MG GBM cell lines treated with CCF-NLs showed potential antiproliferative effects. Regarding the underlying mechanisms of inducing apoptosis in DBTRG-05MG GBM cells, CCF-NLs were shown to downregulate the expression of antiapoptotic B-cell lymphoma/leukemia 2 (Bcl-2), an apoptosis-related protein family member, but the expression of proapoptotic Bcl-2-associated X protein was enhanced compared with that in controls. CCF-NLs also inhibited the activity of caspase-3 and -9, which is the initiator caspase of the extrinsic and intrinsic apoptotic pathways. Blockade of caspase activation consistently induced apoptosis and inhibited growth in CCF-NL-treated DBTRG-05MG cells. This study further investigated the role of the Akt pathway in the apoptotic cell death by CCF-NLs, showing that CCF-NLs deactivated Akt. Specifically, CCF-NLs downregulated the expression of p-Akt and SIRT1 as well as the level of phosphorylated p53. Together, these results indicated SIRT1/p53-mediated cell death was induced by CCF-NLs, but not by extracellular signal-regulated kinase, in DBTRG-05MG cells. Overall, this study suggested caspase-dependent activation of both the intrinsic and extrinsic signaling pathways, probably through blockade of the SIRT1/p53-mediated mitochondrial and Akt pathways to exert the proapoptotic effect of CCF-NLs in DBTRG-05MG GBM cells. Keywords: Cotinus coggygria flavonoid nanoliposomes, cell death, SIRT1, mitochondrial, PI3K/Akt pathway